1951
DOI: 10.1113/jphysiol.1951.sp004565
|View full text |Cite
|
Sign up to set email alerts
|

The absorption of acetate, propionate and butyrate from the rumen of sheep

Abstract: When solutions of sodium acetate, propionate and butyrate are placed separately in the empty rumen of sheep anaesthetized with nembutal, analysis of the blood leaving the rumen shows that absorption of the acids occurs and that the rate of absorption appears to decrease as the molecular size increases (Barcroft, McAnally & Phillipson, 1944).. Recently this was reinvestigated by Gray (1948), who concluded that no absorption at all occurred from the rumen of sheep when the pH was slightly alkaline as would be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
2

Year Published

1954
1954
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 3 publications
5
68
2
Order By: Relevance
“…The marked reduction in volatile fatty acid absorption rate due to a decrease in the acidity of the solution from acid to alkaline (Table 7) was expected from the results of other workers (Danielli et al 1945;Masson and Phillipson 1951).…”
Section: Disoussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The marked reduction in volatile fatty acid absorption rate due to a decrease in the acidity of the solution from acid to alkaline (Table 7) was expected from the results of other workers (Danielli et al 1945;Masson and Phillipson 1951).…”
Section: Disoussionsupporting
confidence: 74%
“…This was done to show any consistent differences in the rate of absorption occurring during period 1 compared with period 2 due to deterioration in the preparations with time. Masson and Phillipson (1951) found that the rate of absorption of volatile fatty acids from the washed-out rumen decreased with time.…”
Section: (B) Feedmentioning
confidence: 99%
“…One probable explanation of some of these differences was provided by the work of Masson and Phillipson (1951). When they deter mined absorption by measuring the disappearance of the VFA from the rumen contents, they found butyrate to be absorbed faster than the other two acids.…”
Section: Structure Of the Rumenmentioning
confidence: 99%
“…Gray (1948) could measure no appreciable absorption at an alkaline pH and suggested that the results of Danlelll _et al ( 1945) were not outside the range of experimental error. However, Masson and Phillipson (1951) demonstrated conclusively that absorption could occur from rumen contents at a pH greater than 7.0. More limited results by and Armstrong et al (1961) supported the contention of Danlelll .et al ( 1945) that absorption is reduced as the pH rises.…”
Section: Structure Of the Rumenmentioning
confidence: 99%
See 1 more Smart Citation